THE APPLICATION OF ROLE PLAYING MODEL IN SOCIAL LEARNING ON GRADE IV STUDENTS’ AT SUNGAI HITAM ELEMENTARY SCHOOL - Nanda Farira; Andriana Sofiarini; Tio Gusti Satria (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine completeness of student learning outcomes after the application of role playing model in Social learning on grade IV students at Sungai Hitam Elementary School. The method used in this research is Pre-Experimental Design. The population in this study is all grade IV of Sungai Hitam Elementary School. The research sample was taken using simple random sampling technique. Data collection techniques in the study using the test. Then the data were analyzed using the t-test. Based on the results of research and discussion it is known that the average value () of pre-test is 40,12 and the average value () of post-test is 77,71. The collected data is then analyzed using the t-test obtained tcount (3,34) ttable (1,75). It can be concluded that the learning outcomes of grade IV students’ at Sungai Hitam Elementary School after the application of role playing model in Social learning completed significantly.